2022
DOI: 10.3390/polym14071288
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable and Biocompatible Thermoplastic Poly(Ester-Urethane)s Based on Poly(ε-Caprolactone) and Novel 1,3-Propanediol Bis(4-Isocyanatobenzoate) Diisocyanate: Synthesis and Characterization

Abstract: A series of non-toxic biodegradable and biocompatible polyurethanes bearing p-aminobenzoate moieties are presented. The introduction of this attractive motif was carried out by the synthesis of a novel isocyanate. These biodegradable polymers were chemically and physically characterized by several techniques and methods including bioassay and water uptake measurements. The molecular weight of the soft segment (poly-ε-caprolactone, PCL) and hard segment crystallinity dictated the mechanical behavior and water u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Polyurethane and hybrid confirmations Similar to previous studies 9,10 , PCL with two terminated hydroxyl groups at opposite ends, namely, PCL-diol, was used as the polyol to synthesize biodegradable PU. The diol groups were reacted with HDI, a diisocyanate, to produce urethane bonds between the PCL-diols and polyurethane 12,13 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethane and hybrid confirmations Similar to previous studies 9,10 , PCL with two terminated hydroxyl groups at opposite ends, namely, PCL-diol, was used as the polyol to synthesize biodegradable PU. The diol groups were reacted with HDI, a diisocyanate, to produce urethane bonds between the PCL-diols and polyurethane 12,13 .…”
Section: Resultsmentioning
confidence: 99%
“…The developed PU was thermoplastic and biodegradable as a result of polymerization with polycaprolactone (PCL)-diol, hexamethylene diisocyanate (HDI), and (3-aminopropyl) triethoxysilane (APTES). PCL-diol and aliphatic HDI have been used to synthesize thermoplastic, biodegradable, and biocompatible PUs 9,10 . A thermoplastic polymer was required for the sol-gel process since polymers must exist in a sol state before forming covalent bonds with the silica network.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous studies 9,10 , PCL with two terminated hydroxyl groups at opposite ends, namely PCLdiol, was used as the polyol to synthesize biodegradable PU. The diol groups were reacted with HDI, a diisocyanate, to produce urethane bonds between the PCL-diols and polyurethane 11,12 .…”
Section: Polyurethane and Hybrid Con Rmationsmentioning
confidence: 93%
“…The developed PU was thermoplastic and biodegradable as a result of polymerization with polycaprolactone(PCL)-diol, hexamethylene diisocyanate (HDI), and (3-aminopropyl)triethoxysilane (APTES). PCL-diol and aliphatic HDI have been used to synthesize a thermoplastic, biodegradable, and biocompatible PU 9,10 . The introduction of (3-aminopropyl)triethoxysilane (APTES) during polymerization allowed for the functionalization of the PU with alkoxysilane groups, which enabled covalent bonding to the silica network.…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory properties mainly include biocompatibility, biodegradation, and mechanical properties [ 41 ]. Many studies have shown that PCL has certain biocompatibility and degradability [ 23 , 42 ], in which the porous structure makes a specific contribution because appropriate pore size is conducive to the invasion and growth of cells and tissues into the scaffold, and finally, the completion of regeneration and repair. The size of molten salt or sugar particles directly determines the pore size of the porous structure in SMPs.…”
Section: Smps and Their Properties In Response To Different Stimulationsmentioning
confidence: 99%